2014
DOI: 10.3109/15376516.2014.956909
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract-induced BEAS-2B cell apoptosis and anti-oxidative Nrf-2 up-regulation are mediated by ROS-stimulated p38 activation

Abstract: Cigarette smoke contains reactive oxygen (ROS) that can cause oxidative stress. It increases the number of apoptotic and necrotic lung cells and further induces the development of chronic airway disease. In this study, we investigated the effects of cigarette smoke extract (CSE) on apoptosis in human bronchial epithelial cells (BEAS-2B). CSE exposure induced ROS generation and p38 mitogen-activated protein kinase (MAPK) activation that are associated with the activation of apoptosis-regulating signal kinase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Therefore it may be assumed that Nrf2 signaling pathway may be connected with MAP Kinase pathway through p38. This observation corroborates the recent finding that Nrf2 was directly influenced by p38 and ROS (Lin et al, 2014).…”
Section: )supporting
confidence: 94%
“…Therefore it may be assumed that Nrf2 signaling pathway may be connected with MAP Kinase pathway through p38. This observation corroborates the recent finding that Nrf2 was directly influenced by p38 and ROS (Lin et al, 2014).…”
Section: )supporting
confidence: 94%
“…therapeutic target for COPD due to its regulation of p38 (31,59) and possible involvement in bronchitis-related cell turnover, as determined in studies with bronchiolar cell lines (60). To assess the role of ASK1 in CS-induced p38 activation and apoptosis, we used a loss-of-function approach.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al. () showed that CSE‐induced apoptosis in BEAS‐2B cells was regulated by the ASK‐1/p38 signalling cascade. Another study on BEAS‐2B cells showed that CSE‐induced upregulation of inflammatory cytokines was dependent on the ERK/p38 signalling pathway (Li D et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increased level of activated p38 was observed in pulmonary fibroblasts exposed to CSE (Kim et al, 2011). Lin et al (2014) showed that CSE-induced apoptosis in BEAS-2B cells was regulated by the ASK-1/p38 signalling cascade. Another study on BEAS-2B cells showed that CSE-induced upregulation of inflammatory cytokines was dependent on the ERK/p38 signalling pathway (Li D et al, 2016).…”
Section: Activation Of Mapks By Csementioning
confidence: 92%